Investigating the Findings of Chest X-ray and CT Scan in Leptospirosis with or without Pulmonary Manifestations and its Treatment in Razi Qaemshahr Hospital - Ahmad Alikhani; Zohreh alinasab; Negar Feyzi; Masoomeh Abdi Talarposhti; Hadi Majidi (Journal of Mazandaran University of Medical Sciences, 2024)
Background and purpose: Leptospirosis is a common disease between humans and animals, the source of which is rodents, canines, etc., the disease is transmitted by scratching the skin and getting it contaminated with water contaminated with animal urinary waste and is currently an endemic disease in neighboring northern provinces of Iran. The purpose of this study was to investigate the findings of chest X-ray and lung CT scans in leptospirosis with or without pulmonary symptoms. Materials and methods: The current descriptive and retrospective research examined the findings of chest X-ray and CT scan of the lungs in patients with leptospirosis with or without pulmonary manifestations in Razi Ghaemshahr Hospital. In this study, 49 hospitalized patients were randomly selected from the records of leptospirosis patients in Razi Ghaemshahr  Hospital during the spring and summer of 2017 from an information form based on clinical epidemiological characteristics and risk factors for leptospirosis patients using the mentioned characteristics. The disease was prepared in the infectious reference books and articles published in Farsi and English about this disease, and help was taken from a radiologist colleague to interpret the findings of the chest X-ray and CT scan of the lungs. After recording in SPSS 16 software, the data were analyzed through a Q_Q graph and skewness index. The clinical and epidemiological findings of leptospirosis were considered as inclusion criteria in the study, and the absence of serological tests to confirm leptospirosis was considered as exclusion criteria. Results: Among 49 hospitalized patients with leptospirosis, 11 patients had abnormal radiological findings and 38 patients had normal X-rays. Among 11 patients with abnormal radiological findings, 6 patients had respiratory symptoms, which included 54.54% cough and 18.18% bloody sputum. Among 38 patients with normal radiography, 11 patients had pulmonary symptoms, which included 29.94% cough and 2.63% bloody sputum. The amount of cough was significantly higher. Abnormal findings in chest X-ray, alveolar infiltration, ground glass opacity, and consolidation were the most frequent in the CT scan of the lung. Conclusion: Considering the significant percentage of normal chest radiographs in patients suffering from rice field fever with pulmonary symptoms, it is essential to perform a CT scan of the chest and decide on more effective therapeutic interventions. Therefore, it is considerable that usually changes in the chest CT scan in the severe form of the disease that causes vasculitis and alveolar bleeding appear before the appearance of severe symptoms such as bloody sputum and make a decision to start more effective drugs in the patient's treatment plan.  As a result, pulmonary involvement in patients with leptospirosis is of special importance and it should be given special attention due to the endemicity of leptospirosis in the province, considering the associated complications and high mortality and the possibility of its occurrence even in patients who do not have respiratory complaints at the time of presentation. It is suggested to conduct more extensive research based on the population in this field.